(3JWhQ eYGjjQ GdJObjb h GdJCcjO GdOhdjI h bhGYO GNdGbjGJ GdegfI (B/s - (3LeYI, GMeO Mdejs ((3YeGf(B: s (3OGQ UaGA ddfTQ(B, s, 2009)
(3JbQjQ GdJObjb ddZQV GdYGe (B-(3GdJYOjdGJ Ydi JbQjQ GdJObjb (B-(3JbQjQ GdJObjb dZQV NGU (B-(3GdJbQjQ Ohf GdGeJKGd (B(IFRSs) -(3GdJbQjQ HTCf GdGQbGe GdebGQfIs
(3SdSdI GdcJH GdegfjIs
Keywords: (3GNdGbjGJ GdegfIs; (3GdJCcjOs; (3GdJObjbs; (3GdeMGSHIs; (3GdeMGSHI GdOhdjIs; (3JObjb GdMSGHGJs